Pushing past the human in Latin American cinema - Fornoff, Carolyn; Heffes, Gisela, 1971- (State University of New York Press, 2021)
"Sheds light on emergent Latin America cinema that addresses the politics of environmental destruction, the uneveness of climate change consequences, and new ways of visualizing the world beyond the human"-- Provided by publisher.
Keywords: Motion pictures -- Latin America -- History.; Climatic changes in motion pictures.; Ecology in motion pictures.; Cinéma -- Amérique latine -- Histoire.; Climat -- Changements, au cinéma.; PERFORMING ARTS / Film & Video / History & Criticism.; Climatic changes in motion pictures; Ecology in motion pictures; Motion pictures; Latin America; History